Exploring residents’ perspectives on their professional identity in general practice residency in the Netherlands: a qualitative study - Mattijs E Numans; Walther NKA van Mook; Miami Al-Sabiry; Irene Slootweg; Pieter Barnhoorn (BMJ Open)
Objectives Educational initiatives in residency may lack alignment with residents’ learning objectives. Furthermore, they may overlook residents’ struggle to find fulfilment in their work. Professional identity formation (PIF) is a conceptual lens through which to explore the alignment of educational initiatives with residents’ learning objectives. Few empirical studies have examined PIF in residency in general. PIF outcomes in general practice (GP) residency, from the perspective of residents, are poorly represented in the current literature. This study aimed to explore residents’ perspectives on their professional identity to inform PIF learning objectives in GP residency.Design A qualitative descriptive study using a list of predetermined questions to guide focus group interviews.Setting Data collection took place between winter and autumn 2019 at four GP training institutes across the Netherlands.Participants 92 third (final) year GP residents participated in focus group interviews.Results Residents’ overall perspectives hinged on how to negotiate the endlessness of the profession. This endlessness was reported to manifest in four areas, namely, the GP: as an accessible healthcare provider, as a spider in the care-web, providing personalised care and maintaining a work–life balance.Conclusions GP residents’ narratives highlighted an increasingly challenging profession and posited the importance of guided negotiation for their PIF. Deploying the concept of subjectification in residents’ guided negotiation of the profession’s endlessness possibly improves the supervisor–resident educational alliance. Furthermore, awareness of issues related to work–life balance and fostering residents’ sense of belonging and collegiality may contribute to improving their well-being and sense of fulfilment in their work.